1991
DOI: 10.1002/pssb.2221680206
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Range Order and Solid Solution Hardening

Abstract: A Monte-Carlo simulation is made of the short-range order in Ta-0 with oxygen-oxygen long-range strain-induced potential with the exception of the first coordination shell. In a wide temperature range short-range order of cluster type is discovered. On the basis of dislocation-obstacle interaction models the start stress of (1/2)(111){110} screw dislocations in the solid solution with clusters is calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…It is easily shown that in such case the Fermi Surface (FS) undergoes a change of its topology. Thus, according to the ETT theory [1][2][3][4][5][6], the electronic density of states (DOS) may be written as the sum of a regular term, no (E), related to metal bands not responsible for the ETT, and a special term, n1(E), i.e. (1) The special term in eq.…”
Section: -Electronic Topological Transitions and Deviations From Vegamentioning
confidence: 99%
See 4 more Smart Citations
“…It is easily shown that in such case the Fermi Surface (FS) undergoes a change of its topology. Thus, according to the ETT theory [1][2][3][4][5][6], the electronic density of states (DOS) may be written as the sum of a regular term, no (E), related to metal bands not responsible for the ETT, and a special term, n1(E), i.e. (1) The special term in eq.…”
Section: -Electronic Topological Transitions and Deviations From Vegamentioning
confidence: 99%
“…(7) is smeared out at any T > 0, due to the the Fermi function, in eq. (6), and even at zero temperature [3,5], by disorder effects introduced by alloying (finite lifetimes). In random alloys, the effects on the equilibrium volume per atom VS. concentration curve, V (N), can be studied by minimisation of the free energy with respect to the volume at fixed atomic concentration.…”
Section: -Electronic Topological Transitions and Deviations From Vegamentioning
confidence: 99%
See 3 more Smart Citations